Postsynaptic density protein 95-regulated NR2B tyrosine phosphorylation and interactions of Fyn with NR2B in levodopa-induced dyskinesia rat models - Ba M; Kong M; Ma G (Dove Medical Press, 2014)
Maowen Ba,1,* Min Kong,2,* Guozhao Ma3 1Department of Neurology, Yuhuangding Hospital, Yantai City, Shandong, People’s Republic of China; 2Department of Neurology, Yantaishan Hospital, Yantai City, Shandong, People’s Republic of China; 3Department of Neurology, Shandong Provincial Qianfoshan Hospital, Shandong University, Shandong, People’s Republic of China *These authors contributed equally to this work Context: Abnormality in interactions between N-methyl-d-aspartate (NMDA) receptor and its signaling molecules occurs in the lesioned striatum in Parkinson’s disease (PD) and levodopa-induced dyskinesia (LID). It was reported that Fyn-mediated NR2B tyrosine phosphorylation, can enhance NMDA receptor function. Postsynaptic density protein 95 (PSD-95), one of the synapse-associated proteins, regulates interactions between receptor and downstream-signaling molecules. In light of the relationship between PSD-95, NR2B, and Fyn kinases, does PSD-95 contribute to the overactivity of NMDA receptor function induced by dopaminergic treatment? To further prove the possibility, the effects of regulating the PSD-95 expression on the augmented NR2B tyrosine phosphorylation and on the interactions of Fyn and NR2B in LID rat models were evaluated.Methods: In the present study, parkinsonian rat models were established by injecting 6-hydroxydopamine. Subsequently, valid PD rats were treated with levodopa (50 mg/kg/day with benserazide 12.5 mg/kg/day, twice daily) intraperitoneally for 22 days to create LID rat models. Then, the effect of pretreatment with an intrastriatal injection of the PSD-95mRNA antisense oligonucleotides (PSD-95 ASO) on the rotational response to levodopa challenge was assessed. The effects of pretreatment with an intrastriatal injection of PSD-95 ASO on the augmented NR2B tyrosine phosphorylation and interactions of Fyn with NR2B in the LID rat models were detected by immunoblotting and immunoprecipitation. Results: Levodopa administration twice daily for 22 days to parkinsonian rats shortened the rotational duration and increased the peak turning responses. The altered rotational responses were attenuated by PSD-95 ASO pretreatment. Meanwhile, PSD-95 ASO pretreatment decreased the level of PSD-95 protein expression and reduced both the augmented NR2B tyrosine phosphorylation and interactions of Fyn with NR2B triggered during the levodopa administration in the lesioned striatum of PD rats. However, the protein levels of Fyn and NR2B showed no difference under the above conditions. Conclusion: The data demonstrate that the inhibition of PSD-95 protein expression suppressed the interactions of Fyn with NR2B and NR2B tyrosine phosphorylation and subsequently downregulated NMDA receptor overactivation, thus providing benefit for the therapy of LID. Therefore, PSD-95 is important for overactivity of NMDA receptor function due to facilitating NR2B tyrosine phosphorylation dependent on Fyn kinase by regulating interactions of Fyn with NR2B under the pathological conditions of LID. Keywords: PSD-95 ASO, NMDA, rotational response